PENERAPAN STRATEGI PEMBELAJARAN POINT COUNTER POINT (PCP) DALAM MATA PELAJARAN FIQH DI KELAS VIII-A MTS NEGERI 1 PAMEKASAN - Rohmah, Nurul Hidayatur; Arif, Saiful (IAIN Madura, 2024)
ABSTRACT Learning strategies are planned and structured efforts including the use of methods and untilization of various existing resources in the learning process. Strategy Point Counter Point (PCP) is a way in the learning process that gives students the opportunity to be active in arguing from problems that exist in learning. Listen, using learning applications such as Point Counter Point (PCP), it is hoped that students can expand ideas, exchange ideas between friends and as additional strategies in learning activities in class. Although it does not rule out the possibility that implementing this strategy has its own advantages and disadvantages.